Candi Cangkuang dan Masjid Agung Manonjaya Survei Kesejarahan Cagar Budaya di Jawa Barat - Nurhasan Nurhasan (Buletin Al-Turas, 2007)
Among the most concrete. objective. authentic and unique historical evidences are the archeologist inheritance, whether temple, grave, epigraphy. artefac. and other things that support the truth and validity as a historical event. Cangkuang Temple is the one of concrete evidence in West Java as exsist as Central and East Java. This discovery is break the historian and archeologist'sopinion who determines that the kinos in West Java has no tradition to build the big monumental building as temple. Beside that a number of inheritance from lslam period. such as grave and a group of traditional houses which include an interesting etnographic object resource are needed to be conservated.